Pengembangan Sistem Informasi Geografis berbasis Web untuk Kesesuaian Lahan Kawasan Perkotaan di Kabupaten Sidoarjo - Andrian Santiyon; Fatwa Ramdani; Bondan Sapta Prakoso (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
Sidoarjo Regency is an area that has very good and strategic investment land in the East Java region. This can be proven by the amount of investment that comes in from 2014-2018 has always increased. This amount of investment is not matched by the amount of land available for new investors, especially in the city center of Sidoarjo Regency. Sidoarjo Regency Government seeks to develop urban areas throughout the districts of Sidoarjo Regency. The existence of this urban area is needed to meet the availability of land for new investors who want to invest in the city center of Sidoarjo Regency. This research developed a geographic information system to determine the suitability of land in an urban area in Sidoarjo Regency using Multi-Criteria Evaluation and AHP methods. Criteria such as urban settlements, social services, and economic activity are used in this research based on the regulation of the Minister of Home Affairs of the Republic of Indonesia number 57 of 2010 on Guidelines and Standards for Urban Services. The result of this research indicates that the land area of 385,831 km2 (54.21%) is very suitable to use an urban area of Sidoarjo Regency. Only 2.08% of land in Sidoarjo Regency stated not suitable. The result of accuracy testing using receiver operator characteristic method to analyze result model stated pretty well.